2012
DOI: 10.1097/mpa.0b013e31823c0b05
|View full text |Cite
|
Sign up to set email alerts
|

Value of Cytodiagnosis Using Endoscopic Nasopancreatic Drainage for Early Diagnosis of Pancreatic Cancer

Abstract: Cytodiagnosis of pancreatic juice using ENPD multiple times proved to be useful in the diagnosis of pancreatic carcinoma in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
116
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 29 publications
(16 reference statements)
2
116
0
Order By: Relevance
“…Recently, there have been some reports of cytodiagnosis multiple times using PJ obtained by ENPD. The sensitivity and accuracy for diagnosis of PCIS using this method was 100%, and 95%, respectively 64, 70, 71. Current Japanese CGL for PC recommends cytodiagnosis multiple times using PJ during ERCP when localized stenosis of MPD is observed by MRCP, EUS, or ERCP 14…”
Section: Diagnosis Of Pcismentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, there have been some reports of cytodiagnosis multiple times using PJ obtained by ENPD. The sensitivity and accuracy for diagnosis of PCIS using this method was 100%, and 95%, respectively 64, 70, 71. Current Japanese CGL for PC recommends cytodiagnosis multiple times using PJ during ERCP when localized stenosis of MPD is observed by MRCP, EUS, or ERCP 14…”
Section: Diagnosis Of Pcismentioning
confidence: 88%
“…Localized pancreatitis with infiltration of inflammatory cells, fibrosis, and fatty infiltration were frequently observed in the parenchyma around PCIS and atypical epithelium. In addition, there were some PCIS cases with intraductal spread, and mismatch of cancer and MPD stenosis 56, 63, 64, 65, 66, 67, 68, 69. EUS could detect localized pancreatitis, fibrosis, and fatty infiltration around PCIS as a slightly low echoic lesion 56, 66.…”
Section: Diagnosis Of Pcismentioning
confidence: 99%
“…However, EUS seems to be invasive, and the diagnostic ability of EUS to detect early‐stage concomitant PDAC largely depends on the operator's skill; thus, EUS cannot be carried out at the same level globally. Other Japanese investigators62, 63 have demonstrated the important roles of pancreatic juice cytology under ERCP to diagnose stage 0 or I PDAC, although ERCP is still associated with a risk of pancreatitis and is therefore unsuitable for screening. Nevertheless, establishment of a surveillance protocol using an adequate combination of EUS/ERCP for high‐risk patients would contribute to an increase in the number of patients who are diagnosed with resectable concomitant PDAC.…”
Section: Surveillance For Ipmn Without Pancreatectomymentioning
confidence: 99%
“…The results of ENPD cytodiagnosis and PC diagnosis showed a sensitivity of 100 %, a specificity of 83.3 %, and an accuracy of 95 %. In these 20 patients, no acute pancreatitis after ENPD tube placement occurred [51]. For the early diagnosis of PC with long-term survival, clinical guidelines for PC (2013) recommend the following: First, dilatation of the MPD and the presence of cysts are important indirect signs.…”
Section: Diagnosis Of Pancreatic Carcinoma In Situmentioning
confidence: 99%
“…Ikeda et al [49] reported the value of balloon spot pancreatography for the diagnosis of small pancreatic tumors and the possibility of diagnosing PCIS located at the branch ducts. As for pathological findings of PCIS using resected specimens, localized pancreatitis has been reported in the parenchyma around PCIS and atypical epithelium [50][51][52]. EUS may make possible the diagnosis of localized pancreatitis around PCIS as a slightly low echoic lesion [47].…”
Section: Diagnosis Of Pancreatic Carcinoma In Situmentioning
confidence: 99%